Impact of telephone follow-up on COPD outcomes in pulmonary rehabilitation patients: A randomized clinical trial - Stefanie Tonguino Rosero; Juan Carlos Ávila Valencia; Jhonatan Betancourt Peña (Canadian Journal of Respiratory Therapy)
# Background